2021
DOI: 10.3390/jcm10194296
|View full text |Cite
|
Sign up to set email alerts
|

Performing Microdissection Testicular Sperm Extraction: Surgical Pearls from a High-Volume Infertility Center

Abstract: Microdissection testicular sperm extraction (mTESE) has been demonstrated to be the gold-standard surgical technique for retrieving testicular sperm in patients with non-obstructive azoospermia (NOA) as it enables the exploration of the whole testicular parenchyma at a high magnification, allowing the identification of the rare dilated seminipherous tubules that may contain sperm, usually surrounded by thinner or atrophic tubules. MTESE requires a skilled and experienced surgeon whose learning curve may greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…All mTESE procedures were performed by the same urologist (GMC) under general anesthesia as previously described 8 . Briefly, the testis was opened like a book by a gradual and very gentle separation of the lobular tissue of both sides, to minimize tissue stretching and to preserve the caliber of the underlying STs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mTESE procedures were performed by the same urologist (GMC) under general anesthesia as previously described 8 . Briefly, the testis was opened like a book by a gradual and very gentle separation of the lobular tissue of both sides, to minimize tissue stretching and to preserve the caliber of the underlying STs.…”
Section: Methodsmentioning
confidence: 99%
“…under general anesthesia as previously described. 8 Briefly, the testis was opened like a book by a gradual and very gentle separation of the lobular tissue of both sides, to minimize tissue stretching and to preserve the caliber of the underlying STs. The entire surface of the testicular parenchyma was explored first in search for dilated STs or, when they were not found, for those with a slightly larger diameter compared to that of the surroundings.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…While available data from our center and others strongly support the use of microTESE for the treatment of men with NOA, it is important to consider that this is a technically challenging, microsurgical procedure that requires a skilled and experienced surgeon for optimal outcomes [ 58 ]. In fact, studies have shown that sperm retrieval rates (SRR) are strongly related to the surgeon’s case volume, with significant improvements in SRR seen after 50 cases and more subtle, continued improvements seen after more than 500 cases [ 59 , 60 ].…”
Section: Surgical Management Of Male Infertilitymentioning
confidence: 99%
“…Indeed, there are some issues that may explain these findings. The most important one is that, in patients with NOA, the testicular parenchyma is not rarely characterized by a highly heterogeneous distribution of histologically and functionally distinct seminiferous tubules (STs), so that the retrieval of sperm is mostly dependent upon the skill and experience of the urologist, his/her learning curve being strictly correlated with the outcome of mTESE [ 1 , 2 , 3 ], rather than upon the severity of the spermatogenic dysfunction. In addition, the definition of SSR is not homogeneous among groups: ideally, SSR is defined as the retrieval of an adequate number and quality of sperm for intracytoplasmic sperm injection (ICSI); however, at least in some cases, the difference between successful (positive outcome) and failed sperm retrieval (negative outcome) may not always be as sharp as it should be to avoid the risk of misclassification.…”
Section: Introductionmentioning
confidence: 99%